The Application of ASSRs, P50, and MMN in the Exploration of Cognitive Dysfunction Involving Inputs and Processing in Insomnia Patients - Zhao, Hongwei; Liu, Chang; Wang, Changming; Zheng, Xiangyu; Peng, Yanhui; Lv, Yudan (Frontiers in Human Neuroscience, 2021)
Objective Cognitive dysfunction has been commonly found in patients with insomnia, such as attention, memory, speed of information processing and executive functions. Auditory steady-state responses (ASSRs)、P50、Mismatch negativity（MMN）can meet varied need and estimate such different cognitive dysfunction. Thus, we can examine whether insomnia is associated with different cognitive dysfunction by such multiple ERP tasks. Methods We used polysomnography (PSG) to record such objective PSG parameters. ASSR、P50 and MMN were performed in sequence, different ERP components have been analyzed such as latency or amplitude between insomnia group and control group. And we chosed Person correlation to make correlation analysis between different ERP components and gender, education and sleep characteristics. Results There is a significant gender difference of ASSR latency found in insomnia group, and the similar result has been found in suppression ratio of amplitudes (S2:S1) for P50. Additionally, a significant correlation between sleep characteristics and ASSR、P50 has been found. Furthermore, there was a significant difference of MMN latency between insomnia and control group, and between sleep characteristics and varied MMN parameters as latency and amplitude. Discussion Our results suggested robust electrophysiological abnormalities as ASSR, P50 and MMN in insomnia patients. Such abnormalities included gender difference, education difference, difference in depressive tendency and difference in sleep parameters. That results revealed varied cognitive dysfunction involving inputs and processing in insomnia patients. And at the same time, we have also explored the neuropsychological mechanisms underlying the cognitive dysfunction with such different ERP tasks.